MANAJEMEN KEBUTUHAN INFORMASI DOSEN DALAM MELAKSANAKAN TRI DHARMA PERGURUAN TINGGI (Studi Kasus Pada Jurusan SKI Fakultas Adab IAIN Imam Bonjol Padang) - Nasrul Makdis (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2017)
To run the Tri Dharma of Higher Education, lecturers must at all times be able to access and update information quickly. Thus the lecturer will not miss the latest knowledge and information from students or from the general public. Without mastering information, the lecturer will look passive and "telmi" (late thinking). Especially in this highly competitive information technology era, information becomes very important so that lecturers continuously develop and deepen their knowledge. To meet the information needs of lecturers, it is needed a mechanism for access to information and information availability. Access to information requires the availability of infrastructure (telecommunications, electricity) and devices (hardware and software) as well as mastering the use of computers (computer literacy). the problem that often arises now is that there are several attitudes of lecturers in terms of finding information. There are among lecturers who are always actively seeking and finding various information. Meanwhile there are also lecturers who are passive, in the sense that said lecturer there is no desire in finding new information and knowledge, but it is enough to hold the knowledge as it is. However the situation must be said that every lecturer is not likely to neglect information, because that information is an academic and scientific need.nggi,